ACTIONS OF THE JADIDS TO ESTABLISH JUDICIAL AUTHORITIES IN TURKESTAN - Dilshod Pulatovich, Komolov (PT. Antis International Publisher, 2025)
Objective: This study aims to examine the contributions of Jadid educators in Turkestan toward the establishment of judicial authorities, emphasizing their reformative efforts in the face of sociopolitical challenges. Using a comparative analysis of historical sources and normative legal acts, the research evaluates the historical dynamics and legal frameworks that shaped the judicial landscape during this period. Method: The methods employed include a detailed examination of primary sources and a contextual analysis of legal documents, which provide insights into the socio-legal conditions under the Jadid educators' influence and the subsequent imposition of Soviet authority. Results: The results reveal the dual narrative of reform and suppression, showcasing the Jadid educators' significant role in creating judicial structures, juxtaposed with the violent consolidation of Soviet power. The study uncovers how judicial independence was undermined, with courts transformed into instruments of state control and oppression under the Soviet regime. Novelty: The novelty of this research lies in its focused exploration of the interplay between educational reformers and the judicial system in Turkestan, offering a nuanced understanding of how sociopolitical forces reshaped justice mechanisms during a transformative era.